Tonic Immobility in PTSD: Exacerbation of Emotional Cardiac Defense Response - Norte, Carlos Eduardo; Volchan, Eliane; Vila, Jaime; Mata, Jose Luis; Arbol, Javier R.; Mendlowicz, Mauro; Berger, William; Luz, Mariana Pires; Rocha-Rego, Vanessa; Figueira, Ivan; Souza, Gabriela Guerra Leal de (Frontiers in Psychology, 2019)
Among defensive behaviors, tonic immobility is considered the last defensive resort when life is at extreme risk. Post-Traumatic Stress Disorder (PTSD) is the main psychiatric consequence resulting from exposure to traumatic events. Increasing evidence indicate an association between peritraumatic tonic immobilility and severity of PTSD. Cardiac defense response, a reactivity to perceived danger or threat, has been studied by recording heart rate changes that follows the presentation of an unpredictable intense auditory aversive stimulus The aim of this study was to investigate potential distinctiveness in cardiac defense response among PTSD patients who presented – compared to those that did not - tonic immobility reaction in the laboratory setting. Patients (N=17) completed the tonic immobility questionnaire for signs of immobility elicited by passive listening to their autobiographical trauma script. After a while, they were exposed to an intense white noise, while electrocardiogram was recorded. The heart rate during the 80 seconds after the noise, subtracted from baseline, was analysed. Higher reports of tonic immobility to the trauma script were associated with stronger and sustained heart rate accelerations after the noise. The effects on cardiac defense response add to increasing evidence that some PTSD patients are prone to repeated re-experiences of tonic immobility, which may implicate in a potentially distinct pathophysiology and even a new PTSD subtype.